Rancang Bangun Sistem Kendali AC dengan sensor DHT22 dan PIR Dalam Ruangan Menggunakan Mikrokontroller Arduino Nano - Dedi - Afandi (Jurnal Media Infotama, 2025)
— The use of Arduino Nano microcontroller technology in developing control systems is increasingly popular in various Internet of Things (IoT) based applications. This research aims to design and build an automatic AC control system and movement detection in a room using an Arduino Nano equipped with a DHT22 sensor and a PIR sensor. This system is designed to monitor room environmental conditions and automatically regulate AC operation based on data obtained from these sensors. The research methodology includes the hardware design stage using Arduino Nano as the brain of the system, a DHT22 sensor to monitor air temperature and humidity, and a PIR sensor to detect the presence of people in the room. The use of this technology is expected to reduce AC energy consumption by optimizing operating time based on the presence of people and environmental conditions. The experimental results show that the system developed is able to effectively detect changes in temperature, humidity and the presence of people in the room. In addition, automatic control of air conditioning based on sensor data can produce significant energy savings without compromising the comfort of room occupants.